Dual gold/silver catalysis involving alkynylgold(III) intermediates formed by oxidative addition and silver-catalyzed C−H activation for the direct alkynylation of cyclopropenes - Yang, Yangyang; Antoni, Patrick W.; Zimmer, Marc; Sekine, Kohei; Mulks, Florian; Hu, Long; Zhang, Lumin; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2019)
While gold-mediated synergistic catalytic processes involving transmetalations with other metals are well understood, AuI/AuIII cycles in these reactions are rarely reported. Herein a gold-catalyzed direct alkynylation of cyclopropenes is enabled by two operating catalytic cycles, an oxidative catalytic cycle involving an alkynyl AuIII complex formed by oxidative addition and one involving a silver-mediated C−H activation.